Impact of digital mammography on cancer detection and recall rates: 11.3 million screening episodes in the English National Health Service Breast Cancer Screening Program - Blanks, RG; Wallis, MG; Alison, R; Kearins, O; Jenkins, J; Patnick, J; Given-Wilson, RM (Radiological Society of North America, 2018)
Purpose: To report the impact of changing from screen-film mammography to digital mammography (DM) in a large organized national screening program. Materials and Methods: A retrospective analysis of prospectively collected annual screening data from 2009–2010 to 2015–2016 for the 80 facilities of the English National Health Service Breast Cancer Screening Program, together with estimates of DM usage for three time periods, enabled the effect of DM to be measured in a study of 11.3 million screening episodes in women aged 45–70 years (mean age, 59 years). Regression models were used to estimate percentage and absolute change in detection rates due to DM. Results: The overall cancer detection rate was 14% greater with DM (P < .001). There were higher rates of detection of grade 1 and 2 invasive cancers (both ductal and lobular), but no change in the detection of grade 3 invasive cancers. The recall rate was almost unchanged by the introduction of DM. At prevalent (first) screening episodes for women aged 45–52 years, DM increased the overall detection rate by 19% (P < .001) and for incident screening episodes in women aged 53–70 years by 13% (P < .001). Conclusion: The overall cancer detection rate was 14% greater with digital mammography with no change in recall rates and without confounding by changes in other factors. There was a substantially higher detection of grade 1 and grade 2 invasive cancers, including both ductal and lobular cancers, but no change in the detection of grade 3 invasive cancers.